Physiological and behavioral responses to observing a sibling experience a direct stressor in prairie voles. (3rd July 2020) - Wardwell, Joshua; Watanasriyakul, W. Tang; Normann, Marigny C.; Akinbo, Oreoluwa I.; McNeal, Neal; Ciosek, Sarah; Cox, Miranda; Holzapfel, Nicole; Sujet, Samantha; Grippo, Angela J.
Abstract: Uncontrollable stress precipitates negative mental and physical health outcomes. Furthermore, the vicarious experience of stress (e.g. observing another individual experience a direct stressor) can mimic the effects of directly experiencing the stressor. The current experiment examined the behavioral and physiological effects of the vicarious experience of stress using the socially monogamous prairie vole. Male prairie voles were exposed to either an empty open field chamber, or a chamber in which the animal observed a sibling undergoing a concurrent direct physical stressor (tail suspension test) for five minutes. Exploratory and anxiety-like behaviors were recorded in all observers during the test session. Cardiac indices of heart rate and heart rate variability were recorded in a subset of observers prior to, during, and following the test session. Corticosterone levels were measured in all observers and siblings following the test session. When compared to animals exposed to an empty open field chamber, animals that observed a sibling undergo a direct physical stressor exhibited increased heart rate and circulating corticosterone, and decreased heart rate variability. These physiological stress indicators were supported by behavioral changes, including increased freezing followed immediately by orienting of the head toward the center of the apparatus, and decreased locomotion, grooming, and rearing. These preliminary results suggest that prairie voles experience stress vicariously, and provide a foundation for additional studies focused on the underlying mechanisms of vicarious stress. The use of this model may inform our understanding of the social transmission of stress among social species, including humans. LAY SUMMARY: The experience of stress, including observing stress in a loved one, has negative consequences on mental and physical health. This study used a social rodent (prairie voles) to demonstrate that stress transfers among social individuals, consequently producing an increased physiological and behavioral stress response in prairie voles observing their siblings experience stress. This research informs our understanding of the interactions of social experiences and stress in humans.